Happiness amongst Israel Defense Force (IDF) Mental Health Officers (MHO’s) - Shelef, Assaf (Disaster Mil Med, 2015)
BACKGROUND: Positive psychology is the scientific study of positive experiences and positive individual traits. Happy people have a better quality of life and other benefits, including better health. The Mental Health Department of the IDF employs a large cadre of Mental Health Officers (MHO’s). The rate of burnout among MHO’s is considered to be high. Career satisfaction has received attention recently with publications dealing with the growing discontent of healthcare system workers. High MHO’s satisfaction is likely to result in good outcomes with patients. Continued state of dissatisfaction, may result in health problems. In this study we tried to assess levels of happiness and its correlates among MHO’s. METHODS: Survey among MHO’s. Participants answered a questionnaire including the Satisfaction with Life Scale (SLS);personal details: sex, age, marital status, number of children, family income, state of healthand military details:seniority as MHO, rank, administrative executive or clinical position, unit type, army service placement. RESULTS: In the period of the survey100 MHO’s completed the questionnaire. Amongst them were 14 psychiatrists, 25 psychologists and 60 social workers. Mean age 37.37 ± 7.12 years, mean years in army service 7.83 ± 6.47. 44% of the MHO’s were Captains, 44% Majors, 3% Lieutenant Colonels and 8% citizens working for the I.D.F. The SLS score was analyzed in order to identify correlations to demographic and clinical variables and Pearson coefficient correlations were calculated. The mean total SLS score was 24.29 ± 5.22. The only statistically significant association with SLS score was family income (p = 0.0109). CONCLUSIONS: MHO’s reported similar levels of happiness as the mean score found in an Israeli national survey and slightly higher level of happiness compared to Israeli physicians. Family income was found to be associated to the level of happiness. Army rank and unit type were not associated with higher satisfaction with life.